Different Strokes? : Common and Uncommon Responses to Financial Crises - Boughton, James (IMF Working Papers; Working Paper, 2001)
Much of the debate about the management of financial crises has focused on structural and psychological issues regarding the conditions that are supposed to be necessary to restore investor confidence. Nonetheless, the paramount requirement in the short term is for countries in crisis to adopt correct macroeconomic policies. An analysis of conventional macroeconomic models reveals that countries can afford to run expansionary policies to restore internal balance only if they can afford to ignore the requirements for external balance. This arithmetic does not depend on whether macroeconomic policies were inappropriate before the crisis hit.